1998
DOI: 10.1007/s004670050418
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular hypertension and vascular anomalies in Alagille syndrome

Abstract: Alagille syndrome (AS) is characterized by the association of at least three of the following five abnormalities: chronic cholestasis, peripheral pulmonary artery stenosis, vertebral arch defects, embryotoxon, and typical facies. In addition to urological abnormalities, tubulointerstitial nephritis, renal tubular acidosis, and mesangiolipidosis have been noted in AS. The usual manifestations of such renal pathologies rarely include hypertension. We report five patients with at least four of the five major feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 17 publications
1
37
0
5
Order By: Relevance
“…7,10,12 Renovascular anomalies have been described in a series of 5 patients with AGS. 16 Angiography demonstrated unilateral or bilateral renal artery stenosis in all of these patients who presented with hypertension. In addition, these 5 patients also all had other abnormalities of their large arteries, namely the aorta, celiac artery, superior mesenteric artery, and subclavian artery.…”
Section: Discussionmentioning
confidence: 85%
“…7,10,12 Renovascular anomalies have been described in a series of 5 patients with AGS. 16 Angiography demonstrated unilateral or bilateral renal artery stenosis in all of these patients who presented with hypertension. In addition, these 5 patients also all had other abnormalities of their large arteries, namely the aorta, celiac artery, superior mesenteric artery, and subclavian artery.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, JAG1 mutations are thought to cause multiple organ abnormalities. Renal involvement, such as renal tubular dilatation, agenesis or hypogenesis, and renal tubular acidosis, have been reported in 40~70% of patients with Alagille syndrome [7,8]. Here we report a female patient with Alagille syndrome who manifested severe hypertension caused by renal artery stenosis in a solitary functioning kidney.…”
Section: Introductionmentioning
confidence: 81%
“…Renal artery stenosis has recently been reported in Alagille syndrome. Berard et al reported that renal artery stenosis was a complication in five patients with Alagille syndrome [7]. In two of the five patients, renal artery stenosis was recognized at second angiography, indicating that the stenosis might be progressive.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, renal and vascular defects are seen in a significant percentage of patients. [2][3][4][5][6] ALGS exhibits highly variable expressivity for each of the affected systems, ranging from no apparent clinical involvement to severe disease leading to transplantation or death. 78 Risk of mortality depends on severity of organ involvement, and is most commonly related to congenital heart disease or intracranial bleeding.…”
Section: Introductionmentioning
confidence: 99%